The Role of Social Media in Early Children's Language Acquisition (Psycholinguistic Review) - Lutfi Eksawati; Helmi Seftiani; Dini Nurhayati (Universitas Sebelas Maret, 2021)
The purpose of this study is to explain how social media plays a role in early childhood language learning at Pertiwi 1 Dermaji Kindergarten. This study used a qualitative descriptive research method. In this study, the sample was determined using data collection techniques that focused on specific objectives. The data used came from sources or informants, such as class teachers and several parents of Pertiwi 1 Dermaji Kindergarten students. Data collection was carried out using detailed interview techniques, observation, and document or archive searches. In this study, we utilized interactive data analysis techniques, such as data reduction, data presentation, and drawing conclusions or verification. From the results of the study, it was revealed that the acquisition of a second language by Pertiwi 1 Dermaji Kindergarten students was supported by constant interaction in the family environment, as well as the positive impact of the development of social media which is currently growing.